Knowledge of Early Childhood‘s Mothers Regarding Toilet Training at Primary Health Care Centers in Alrusafa District in Baghdad City - Ahmed Abd-Alkadeem Mohammed; Eqbal Ghanim Ali (Institute of Medico-legal Publications Pvt Ltd, 2021)
Toilet training refers to the acquisition of skills necessary for controlling of both the bowel and bladder forthe right use of toilet by child at appropriate age and time. A descriptive study (cross-sectional design)wasused; To aseess the Knowledge of early childhood‘s mothers Regarding Toilet Training and to find out therelationship between between the knowledge of early childhood‘s mothers’ demographic variables such as(age, educational level, occupational status et al ….) and their child’s demographic variables (age, gender,number of children et al….).Non probability (convenience sample) of (225) early childhood’s mothers (have children’s age between 1-5years).The study concludes that the early childhood’s mothers with moderate border to low level of knowledgeregarding toilet training. No significant association among parent’s socio-demographical characteristicsandchild’ssocio-demographical characteristics with the knowledge, except between “Starting toilet trainingor not” and knowledge, also significantassociation found between mother’s source of information withthe knowledge. The study recommends that extensive health educational programme should be applied toincrease the early childhood’s mother knowledge regarding toilet training.